Integrated systems approach to enhance rural development: word2vec analysis - Thabile Dube; Arnesh Telukdarie (Cogent Social Sciences)
Rural development plays a pivotal role in global efforts to eradicate extreme poverty, ensure food security, and create sustainable livelihoods. Existing research shows a lack of comprehensive understanding of the interconnections among various systems and subsystems within a rural ecosystem. Although research is done in these systems, there is a lack of quantifiable data to effectively measure and track progress, evaluate interventions, and inform evidence-based decisions in the context of rural development. Through advanced data analysis techniques, the word2vec research aims to quantitatively assess the interconnectedness of various rural subsystems and provide insights that can inform integrated and holistic approaches to rural development. Data from diverse systems such as rural demographics, agriculture, education, electricity/energy, healthcare, science and technology, transport, and water systems are analysed to identify patterns and relationships. The findings reveal significant insights into the interconnected nature of key rural domains. These findings emphasise the necessity for integrated, holistic approaches to rural development.